Gambaran Peran Keluarga Dalam Merawat Lansia Dengan Ketergantungan Di Desa Pabelan - Yuhono, Pujian; , H. M. Abi Muhlisin, S.K.M., M.Kep (2017)
The aging process in the elderly causes appearance the degeneration in physically and mentally. Elderly is a condition characterized by failure of maintaining a balance to physiological stress conditions. This failure is related to degression in the ability to live and decreased sensitivity of individually. The degression is impacted to dependency of elderly with others including the families. The family has an Important Role in caring of elderly to keeping the quality of life. This study is to knowing the description of family's role in caring of the elderly with dependency in pabelan village sukoharjo. This is non-experimental research and using quantitative descriptive design. The population of this study is family who taking care of the elderly with dependency in pabelan village sukoharjo. The sample are 36 families and using quota sampling technique. Collecting data was using a questionnaire and descriptive techniques used to analysis the data. The Conclusion of this research is characteristic of families who living together elderly with dependency are mostly female, 34-40 years old, senior high school graduated and mostly a laborer. The characteristic of dependency level of elderly are mostly light, and family's role in caring of the elderly with dependency in pabelan village are mostly good.